Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Subtema Lingkungan Tempat Tinggalku - Neneng Saidah; Yuyun Elizabeth; Yuli Mulyawati (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of the Problem Based Learning model on the learning outcomes of the environmental sub-theme where I live. This type of research is quantitative research, the type used is quasi-experimental research. The N-Gain calculation for the Problem Based Learning model is 62 with moderate criteria and the N-Gain value for the conventional model is 51 with moderate criteria. So that the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the Conventional model. Researchers also carried out a normality test with the Lilliefors test for both samples with normal distribution. Then in the homogeneity test the data is homogeneous because it is smaller than X2 table, the value is 1.092 ≤ 5.991. Furthermore, in the hypothesis test, it was found that tcount of 2.606 was greater than ttable of 1.99714 indicating that Ho (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. Based on the results of the research above, it can be stated that the Problem Based Learning model has an influence on the learning outcomes of the environment sub-theme where I live in class IV at SDN Sampora 01, Bogor Regency.